Neuroscience and language acquisition and learning: a systematic literature review - María Ángeles Quesada Cubo; Mario Peña Sánchez (Journal of Neuroeducation)
This project explored the intersection between neuroscience and education, focusing specifically on primary education and the acquisition of English as a second/foreign language. Education is a constantly evolving field that benefits from interdisciplinary approaches, including insights from neuroscience. Concentrating on the multidisciplinary field of neuroeducation, the study sought to analyze recent neuroscience findings to enhance teaching and learning processes. This approach was particularly crucial in primary education, where children’s cognitive and linguistic development is highly responsive due to significant neuroplasticity in the brain. Additionally, the research examined how neuroeducation and neurolearning could improve the teaching of English as a second/foreign language. For this purpose, an extensive literature analysis, following the PRISMA systematic review methodology, was conducted to assess relevant papers indexed in the Scopus database that reflected the current state of research in this field. The findings suggested that integrating neuroscience-based techniques could significantly enhance students' linguistic fluency and competence during their formative years. This indicated a paradigm shift in pedagogical practices towards approaches that incorporated a deeper understanding of brain structure and function in education, although further research was needed.